SUFFIX FORMATION OF NAMES OF KITCHEN UTENSILS AND THEIR WORD-FORMATION MODELS IN ENGLISH AND UZBEK (Scientific journal of the Fergana State University, 2026)
This article presents a detailed comparative study of suffixal derivation in the lexical group of kitchen utensil terms in English and Uzbek. The relevance of the research lies in the growing interest in the contrastive analysis of lexical systems, particularly in terminology and everyday vocabulary that reflect the cultural and practical aspects of speakers' lives. As an essential part of daily life, kitchen utensils offer rich linguistic material for analyzing word-formation processes and identifying both universal and language-specific features in vocabulary structure.The study identifies and describes the main suffixal models for forming kitchen utensil terms in English and Uzbek, outlining their semantic and functional properties. A systematic comparative analysis is carried out between the two typologically different languages. This research is the first to identify and classify suffix models specific to this lexical group in each language and to assess their productivity and semantic completeness. The study also explores similarities and differences in suffixal derivation systems between English and Uzbek as they pertain to the formation of kitchen-related terminology.